Gut Akkermansia muciniphila, Prevotellaceae, and Enterobacteriaceae spp. as Possible Markers in Women-Related Nutritional and Clinical Trials: Familial Mediterranean Fever Disease - Astghik Pepoyan (Women's Health Reports)
Background: Studies have shown that the gut microbiota of healthy men and men with familial Mediterranean fever (FMF) disease respond differently to placebo. Given the fact that the composition of the gut microbiota is different in men and women, this study aimed to describe in detail the placebo response of the gut microbiota in healthy and FMF women. Materials and Methods: The bacterial response to placebo was fully evaluated on a previous PhyloChip™ DNA microarray-based assay (GEO Series; accession number GSE111835). Results: The change in the total number of operational taxonomic units in healthy women exposed to placebo is more than that of healthy men, in contrast to FMF people (704 vs. 140 and 409 vs. 7560, respectively [p < 0.05]). Gut Firmicutes diversities are more sensitive to placebo, whereas Akkermansia muciniphila remained unchanged after the placebo administration for both healthy and FMF people. Gut Prevotellaceae and Enterobacteriaceae diversities of healthy subjects and FMF women are also almost unchanged from placebo. Meanwhile, only 56.35% of gut Enterobacteriaceae diversities in FMF men were placebo resistant. Conclusion: The response to a placebo varies depending on a person’s gender and health status. Healthy and FMF women’s placebo study groups could be avoided by excluding placebo-sensitive 704 of 18,725 and 409 of 18,725 bacterial diversities, respectively. Because the placebo causes changes in all gut bacterial phyla in healthy and FMF women, and only the representatives of Enterobacteriaceae and Prevotellaceae families and A. muciniphila spp. are not affected by placebo, these bacteria can be considered as possible markers in women-related nutritional/clinical trials. Data on the response of the gut microbiota in healthy women to placebo might be used in studies of diseases other than FMF. The response of gut bacteria from different taxonomic affiliations to placebo may provide a basis for uncovering the role of these bacteria in the gut–brain axis.